2015
DOI: 10.1177/0003489415574070
|View full text |Cite
|
Sign up to set email alerts
|

USH2 Caused by GPR98 Mutation Diagnosed by Massively Parallel Sequencing in Advance of the Occurrence of Visual Symptoms

Abstract: Objective We present two patients who were identified with mutations in the GPR98 gene that causes Usher syndrome type 2 (USH2). Methods One hundred ninety-four (194) Japanese subjects from unrelated and families were enrolled in the study. Targeted genomic enrichment and massively parallel sequencing of all known non-syndromic hearing loss genes were used to identify the genetic causes of hearing loss. Results We identified causative mutations in the GPR98 gene in one family (two siblings). The patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The initial diagnosis of all mentioned patients did not include retinal defects as in other USH2C patients. In case of family B48, it is likely that the patients of our families (8 and 10 years old) were too young at the time of their initial examination, since visual symptoms usually manifest only in the second decade 55 . In contrast, the members of family A10 were clearly above the manifestation age and had no retinal defects.…”
Section: Discussionmentioning
confidence: 91%
“…The initial diagnosis of all mentioned patients did not include retinal defects as in other USH2C patients. In case of family B48, it is likely that the patients of our families (8 and 10 years old) were too young at the time of their initial examination, since visual symptoms usually manifest only in the second decade 55 . In contrast, the members of family A10 were clearly above the manifestation age and had no retinal defects.…”
Section: Discussionmentioning
confidence: 91%
“…Several adhesion GPRs have been shown to be important for cochlear development. First, mutation of Gpr98 causes moderate to severe congenital hearing loss in humans ( Moteki et al, 2015 ; Bousfiha et al, 2017 ). In mice, Gpr98 (or Very Large G-protein coupled receptor 1, Vlgr1) is required for the assembly of the ankle link complex and in the subsequent bundle development and survival of cochlear hair cells ( McGee et al, 2006 ; Zou et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another aGPCR, VLGR1 (also referred to by ADGRV1, GPR98, MASS1), was first linked to audiogenic seizures in a mouse model and has been found to be linked to Usher syndrome, an autosomal recessive disorder characterized by hearing loss, retinitis pigmentosa, and vestibular dysfunction (Weston et al, ; Hilgert, ; Moteki et al, ; Yang et al, ). Expressed on mature OLs, VLGR1 is also associated with expression of myelin‐associated glycoprotein (MAG) (Shin et al, ), a cell membrane glycoprotein identified as an inhibitor of axon growth in the CNS after injury (McKerracher et al, ; DeBellard et al, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%